61.5.6 problem 6
Internal
problem
ID
[12130]
Book
:
Handbook
of
exact
solutions
for
ordinary
differential
equations.
By
Polyanin
and
Zaitsev.
Second
edition
Section
:
Chapter
1,
section
1.2.
Riccati
Equation.
subsection
1.2.4-1.
Equations
with
hyperbolic
sine
and
cosine
Problem
number
:
6
Date
solved
:
Tuesday, January 28, 2025 at 07:10:27 PM
CAS
classification
:
[_Riccati]
\begin{align*} \left (a \sinh \left (\lambda x \right )+b \right ) y^{\prime }&=y^{2}+c \sinh \left (\mu x \right ) y-d^{2}+c d \sinh \left (\mu x \right ) \end{align*}
✓ Solution by Maple
Time used: 0.015 (sec). Leaf size: 253
dsolve((a*sinh(lambda*x)+b)*diff(y(x),x)=y(x)^2+c*sinh(mu*x)*y(x)-d^2+c*d*sinh(mu*x),y(x), singsol=all)
\[
y = \frac {-d \left (\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\sinh \left (\mu x \right )}{\sinh \left (\lambda x \right ) a +b}d x \right ) \lambda \sqrt {a^{2}+b^{2}}+4 d \,\operatorname {arctanh}\left (\frac {-b \tanh \left (\frac {\lambda x}{2}\right )+a}{\sqrt {a^{2}+b^{2}}}\right )}{\lambda \sqrt {a^{2}+b^{2}}}}}{\sinh \left (\lambda x \right ) a +b}d x \right )+d c_{1} -{\mathrm e}^{\frac {c \left (\int \frac {\sinh \left (\mu x \right )}{\sinh \left (\lambda x \right ) a +b}d x \right ) \lambda \sqrt {a^{2}+b^{2}}+4 d \,\operatorname {arctanh}\left (\frac {-b \tanh \left (\frac {\lambda x}{2}\right )+a}{\sqrt {a^{2}+b^{2}}}\right )}{\lambda \sqrt {a^{2}+b^{2}}}}}{\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\sinh \left (\mu x \right )}{\sinh \left (\lambda x \right ) a +b}d x \right ) \lambda \sqrt {a^{2}+b^{2}}+4 d \,\operatorname {arctanh}\left (\frac {-b \tanh \left (\frac {\lambda x}{2}\right )+a}{\sqrt {a^{2}+b^{2}}}\right )}{\lambda \sqrt {a^{2}+b^{2}}}}}{\sinh \left (\lambda x \right ) a +b}d x -c_{1}}
\]
✓ Solution by Mathematica
Time used: 5.957 (sec). Leaf size: 289
DSolve[(a*Sinh[\[Lambda]*x]+b)*D[y[x],x]==y[x]^2+c*Sinh[\[Mu]*x]*y[x]-d^2+c*d*Sinh[\[Mu]*x],y[x],x,IncludeSingularSolutions -> True]
\[
\text {Solve}\left [\int _1^x-\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \sinh (\mu K[1])}{b+a \sinh (\lambda K[1])}dK[1]\right ) (-d+c \sinh (\mu K[2])+y(x))}{c \mu (b+a \sinh (\lambda K[2])) (d+y(x))}dK[2]+\int _1^{y(x)}\left (\frac {\exp \left (-\int _1^x\frac {2 d-c \sinh (\mu K[1])}{b+a \sinh (\lambda K[1])}dK[1]\right )}{c \mu (d+K[3])^2}-\int _1^x\left (\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \sinh (\mu K[1])}{b+a \sinh (\lambda K[1])}dK[1]\right ) (-d+K[3]+c \sinh (\mu K[2]))}{c \mu (d+K[3])^2 (b+a \sinh (\lambda K[2]))}-\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \sinh (\mu K[1])}{b+a \sinh (\lambda K[1])}dK[1]\right )}{c \mu (d+K[3]) (b+a \sinh (\lambda K[2]))}\right )dK[2]\right )dK[3]=c_1,y(x)\right ]
\]